Veterinary Medical Education: Challenges and Perspectives (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Veterinarians are valued and respected professional figures. Veterinary research transcends species boundaries and includes the study of both spontaneously occurring and experimentally induced models of both human and animal diseases. The COVID-19 pandemic has highlighted the importance of the One Health program, and this adaptive and responsive approach should be implemented in veterinary medical education. These fundamental changes in the roles, responsibilities, and spectrum of activities of veterinary professionals require equal changes, improvements, and adaptations to veterinary science and medical education training programs. These modifications may include, for instance, increasing the participation of veterinary professionals in multidisciplinary human medicine teaching, training, and research teams (i.e., human anatomy, physiology, or biology, among others). Significantly, recent scientific and technological breakthroughs (i.e., RNA-based vaccines, improved molecular diagnostic tools (PCRs), innovative ICTs applied to health assessment and research, etc.) have been seen to influence current teaching and training programs in key, modern, and innovative veterinary colleges and universities.